The impact of international economic institution on production and distribution of surplus values in the XX century and the first years of the XXI center - Lê Thị Thúy Nga (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Economic institutions play a role in economic management, and market economy management tools. The State as an economic institution, in the process of organizing macroeconomic management, simultaneously plays the role of economic management entity in the market economy. The current international economic institution is a formal or informal market economy institution that links countries to address issues such as the enactment and enforcement of laws on production and distribution of value. surplus, creating reform pressures while at the same time facilitating changes, reforms in production and distribution of surplus value to reduce production costs.